A Conceptual Framework for Understanding Multiple Tobacco Product Use and the Impact of Regulatory Action. Issue 3 (20th June 2018) - Pacek, Lauren R; Wiley, Jenny L; McClernon, F Joseph
Abstract: Introduction: Over 35% of the adult tobacco-using population regularly use more than one tobacco product. Although rates of tobacco use in the United States have declined over the last decade, rates of multiple tobacco product (MTP) have either remained stable (among adults) or increased (among youth). Methods: In this paper, we review the literature and propose a framework for understanding both MTP use and how regulatory actions on any single tobacco product (STP) may influence the use of other tobacco products. Results and Conclusions: Within the framework, Product, Person, and Context/Situational factors (and their interactions) influence product cross-substitution and thus patterns of use of MTPs. In addition, we propose that Context/Situation effects specifically increase the complexity of MTP-use patterns resulting in "dynamic complementarity" in addition to substitution-like relationships between tobacco products. Experimentation with, and use of, various tobacco products results in reinforcement histories that affect which products are used, in what contexts, and by whom, which in turn has downstream impacts on toxicant exposure and health. We conclude our analysis with an examination of how regulation of STPs can have impacts on the use of other STP and MTP use and provide research questions for further examining MTP use. Implications: Though rates of tobacco use have declined in the United States, over 35% of the adult tobacco-using population regularly uses more than one tobacco product. This paper provides a framework for understanding MTP use and how regulatory actions on any STP may influence the use of other tobacco products. We conclude our analysis by providing research questions for further examining MTP use.